A Geophysical Approach to the Phenomenon of Ground Fissures at the East Thessaly Basin (Greece) - Alexopoulos, J.; Dilalos, S.; Mitsika, G.; Vassilakis, E; Poulos, S. (25th European Meeting of Environmental and Engineering Geophysics, 2019)
The disastrous phenomenon of aseismic ground fissures along the eastern Thessaly basin has deteriorated since 1989. The main reason for these fissures is the over-pumping, which leads to differential vertical compaction of the aquifer system and subsidence on the land surface. In this paper, we present the results of a combined geophysical survey applied in the area (VES and TEM soundings), in order to investigate the subsurface geological conditions. The geological regime of the area is comprised of the alpine basement, transgression formations and finally a package of post-alpine deposits with respectful thickness. A peudo-3D representation of resistivity maps for several depths of investigation was produced. Additionally, a dataset of deep boreholes was used for the calibration of the geophysical data. All the borehole and sounding interpreted data were grouped into three categories in order to produce the Lithology Model of the area. The alpine bedrock was adumbrated only at the southeast and central part of the basin, where we do not observe ground fissures. The absence of alpine bedrock for depths up to 300 meters, the thick and coarse-grained deposits and finally the over-pumping seem to contribute to the creation of the ground fissures.